Factors associated with the development of early childhood caries among Brazilian preschoolers - Patricia Correa-Faria; Paulo Antonio Martins-Junior; Raquel Goncalves Vieira-Andrade; Leandro Silva Marques; Maria Leticia Ramos-Jorge (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The aim of this study was to assess the prevalence of early childhood caries (ECC) in children and investigate the influence of sociodemographic variables, quality of oral hygiene and child-related aspects. A cross-sectional study was carried out with 593 children aged three to five years. Data were collected through clinical examinations and interviews with parents. Interviews with parents of the children were conducted to acquire information on sociodemographic aspects, breastfeeding, bottle feeding and harmful oral habits. Statistical analysis involved the chi-square test and the Poisson regression. The prevalence of ECC was 53.6%. The occurrence of ECC was greater among children with unsatisfactory oral hygiene (PR: 2.95; 95% CI: 2.42-3.60) and those from a family with a lower monthly household income (PR: 1.62; 95% CI: 1.24-2.10). In conclusion, unsatisfactory oral hygiene and monthly income exerted an influence on the occurrence of ECC among preschoolers.